Business and economics students' self-reports on academic reading in English as L2: A factor analysis - Tamara Sladoljev-Agejev; Svjetlana Kolić-Vehovec; Anamarija Jazbec (Croatian Review of Economic, Business and Social Statistics (CREBSS), 2021)
Adequate reading behaviour is vital for text comprehension across fields. In today's professional environment, a well-developed reading skill is also expected in English as a second language (EL2), which happens already in college, although transition to college-level reading may be difficult even in the first language. It is therefore useful to analyse students' use of reading strategies to facilitate their academic progress. This study investigates the reading behaviour of junior students of business/economics when reading academic texts in EL2. We conducted an exploratory factor analysis (N=134) of a 45-item questionnaire about students' awareness of reading strategies and their reading confidence (i.e. self-perceived competence in text retelling). The majority of the items were based on self-reports found in the literature (Kolic-Vehovec, Bajésanski, 2001; Mokhtari, Reichard, 2002; Taraban, Kerr, Rynearson, 2004) and several items were added to the questionnaire (e.g. questions related to note taking). Five factors were interpretable: four factors related to Metacognitive Awareness of Reading Strategies (Repeated Reading, Monitoring/Regulation, Note Taking and Elaboration) and the fifth factor covering self-perceived competence in text retelling (Reading Confidence). Internal consistency of the factors indicated by standardized Cronbach's alphas were 0.83 (Repeated Reading), 0.80 (Monitoring and Regulation), 0.77 (Note Taking), 0.63 (Elaboration) and 0.75 (Reading Confidence). Three strategies positively correlated with each other (Repeated Reading, Monitoring/Regulation and Elaboration), while negative correlation was found between Note Taking and Reading Confidence. The results provide valuable information on the patterns in student reading as a baseline for further analysis of L2 text comprehension in college.
Keywords: A22; I23; 330; business students; factor analysis; metacognitive awareness; reading strategies